Hydrogenotrophic methanogenesis at 7–12 mbar by Methanosarcina barkeri under simulated martian atmospheric conditions - Rachel L. Harris; Andrew C. Schuerger (Scientific Reports)
Abstract Mars, with its ancient history of long-lived habitable environments, continues to captivate researchers exploring the potential for extant life. This study investigates the biosignature potential of Martian methane by assessing the viability of hydrogenotrophic methanogenesis in Methanosarcina barkeri MS under simulated Martian surface conditions. We expose M. barkeri to sustained hypobaria (7–12 mbar), low temperature (0˚C), and a CO2-dominated gas mixture mimicking the Martian atmosphere. The results demonstrate statistically quantifiable CH4 production under all tested conditions, including at 7–12 mbar. Transcriptomics reveal that low total pressure and temperature did not significantly impact gene expression, highlighting the resilience of M. barkeri. However, atmospheric gas composition, specifically Mars gas with 2.9% pH2, led to significant down-regulation of methanogenesis genes, hindering growth over 14 days. Notably, CH4 production scaled with the partial pressure of H2, revealing that hydrogen uptake affinity is a stronger predictor of habitability and methanogenic potential than favorable Gibbs free energy of reaction. Our findings suggest that Mars’ subsurface could harbor habitable refugia capable of supporting methanogenesis, sustaining microbial life at low metabolic steady states. These insights challenge assumptions about Martian habitability and have implications for astrobiological exploration, planetary protection, and in situ resource utilization for future human missions.